Assessment Of Nutritional Status of Rural Early Adolescent School Girls in Dantan-II Block, Paschim Medinipur District, West Bengal - Maiti, Soumyajit; Chattterjee, Kauhik; Kazi , Monjur Ali; Ghosh, Debidas; Paul, Shyamapada (National Journal of Community Medicine, 2011)
A study was conducted to ascertain the growth and nutritional status of adolescent school girls in rural area. Present study was conducted among adolescent girls studying in 5th to 8th standard (age group of 10 to 14 years) of eighteen government approved school in Dantan-II block, Paschim Medinipur district, West Bengal. Physical growths of total of 3611 girls were assessed through anthropometry. Data on weights and heights of girls were collected using standardized techniques. The extent of malnutrition of adolescent girls was evaluated by well-to-do Indian and NCHS median value. The results revealed that the weights and heights of these girls were below those of standard value. As regards weight for age index, only 28.2% subjects were in the normal category and the percentage of subjects suffering from Grade I (25.7%), Grade II (30.4%), Grade III (13.7%) and Grade IV (1.9%) malnutrition was quite prevalent in present study. With respect to height for age index, 65.2% of the subjects were in the normal category, 32.6% had mild retardation and about 2.2% had poor status. The present study revealed that different grades of malnutrition are widely prevalent among the girls in our study area. All these observations suggest that school going early adolescent girls need better nutrition to combat the problem of under nutrition. Further studies should be made to identify the factors responsible for it.